The yards - Cray, James ([Burbank, Ca.] : Mirama Films [production company] ; Kuala Lumpur : Speedy Video [Distribution], 2001)
Released from prison after taking the fall for a group of his friends, Leo Handler just wants to get his life back on track. But when he takes a job with his powerfully inflential Uncle Frank and reconnects with his old friend Willie, Leo finds himself unwittingly drawn into a world of sabotage, high-stakes payoffs and even murder. Then, he discovers a secret that makes him the target of the city's most ruthless family--his own
Executive producer, Bob Weinstein ; writer, James Gray, Matt Reeves
Cast: Mark Wahlberg, Joaquin Phoenix, Charlize Theron
VCD format
Keywords: Violence in motion pictures; Feature films; Corporations -- Corrupt practices -- drama